3-D electrical structure and tectonic dynamics in the Yangbajing area based on the array magnetotelluric data - Lei, Lulu; Jin, Sheng; Dong, Hao; Wei, Wenbo; Ye, Gaofeng; Zhang, Letian (Frontiers in Earth Science, 2023)
The well-known N-S-trending fault in the Yangbajing area plays a crucial role in the tectonic evolution of the Tibetan Plateau. Previous researches on a few E-W geophysical profiles suggested that the eastern shear at the base of the upper crust and/or lithosphere deformation brought on by asthenosphere upwelling are the major causes of the Yadong-Gulu rift’s creation. Here we propose a 3-D electrical resistivity model derived from the magnetotelluric (MT) array data spanning the Yadong-Gulu rift (YGR), and the distribution of temperature and melt fraction is estimated by the experimental calibrated relationships bridging electrical conductivity and temperature/melt fraction. The result reveals that the Indian slab subducted steeply in the east of the Yadong-Gulu rift, while Indian slab may have delaminated with a flat subduction angle in the west. The temperature distribution shows that the upper mantle of the northern Lhasa terrane is hotter than that of the southern Lhasa terrane. This is likely the result of mantle upwelling caused by either the subduction of the Indian slab or thickened Tibetan lithosphere delamination. Moreover, the strength of the mid-lower crust is so low that it may meet the conditions of the local crust flow in the west-east direction. The local crustal flow and the pulling force from the upwelling asthenosphere jointly contributed to the formation of the Yadong-Gulu rift. These main factors exist in different stages of the evolution of the Yadong-Gulu rift.